2008
DOI: 10.1128/aem.02150-07
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of Human Nisin- and Pediocin-Producing Lactic Acid Bacteria To Reduce Intestinal Colonization by Vancomycin-Resistant Enterococci

Abstract: This study demonstrated the capacity of bacteriocin-producing lactic acid bacteria (LAB) to reduce intestinal colonization by vancomycin-resistant enterococci (VRE) in a mouse model. Lactococcus lactis MM19 and Pediococcus acidilactici MM33 are bacteriocin producers isolated from human feces. The bacteriocin secreted by P. acidilactici is identical to pediocin PA-1/AcH, while PCR analysis demonstrated that L. lactis harbors the nisin Z gene. LAB were acid and bile tolerant when assayed under simulated gastroin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 32 publications
5
100
1
Order By: Relevance
“…In the gut, bacteriocins may help the producer to survive and colonize, and inhibit the closely related competitive strains or pathogens, as well as influence the immune system of the host through their impact on gut microbial populations [80,81]. For instance, a Lactobacillus salivarius strain producing salivaricin P becomes predominant in porcine ileum when administered in combination with other probiotic strains that do not produce bacteriocins [82].…”
Section: Bacteriocinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the gut, bacteriocins may help the producer to survive and colonize, and inhibit the closely related competitive strains or pathogens, as well as influence the immune system of the host through their impact on gut microbial populations [80,81]. For instance, a Lactobacillus salivarius strain producing salivaricin P becomes predominant in porcine ileum when administered in combination with other probiotic strains that do not produce bacteriocins [82].…”
Section: Bacteriocinsmentioning
confidence: 99%
“…Antagonistic activity of the bacteriocin producers against a number of pathogenic or antibiotic-resistant bacterial strains in the gut has been a major focus of gut microbiota studies. Several LAB bacteriocins and/or bacteriocin-producing LAB have been shown to inhibit pathogens such as Listeria monocytogenes [83,84], Clostridium difficile [8587], Staphylococcus aureus [88] and even Salmonella enteritidis [89], Some bacteriocin producers have also been reported to eliminate multidrug- or vancomycin-resistant enterococci [81,90]. Therefore, the production of bacteriocins may contribute to the beneficial activities in the gut.…”
Section: Bacteriocinsmentioning
confidence: 99%
“…The inhibition of the pathogen was shown to be the direct result of the production of the two-peptide bacteriocin Abp118, as it was demonstrated that a non-bacteriocin-producing isogenic derivative failed to protect mice from infection. Similarly, the bacteriocinproducing human isolates P. acidilactici MM33 and L. lactis MM19 were shown to reduce vancomycin-resistant enterococci (VRE) populations in vivo (41). P. acidilactici MM33 produces the bacteriocin pediocin PA-1/AcH, while L. lactis MM19 produces the bacteriocin nisin Z.…”
Section: Bacteriocin Function: An Ecological Perspectivementioning
confidence: 99%
“…Based on this premise, probiotic LAB have been positioned in the vanguard of healthcare applications. Probiotic LAB can prevent pathogen colonization in the intestine by occupying sites and producing bacteriocins and other metabolites (Gopal et al, 2001;Lee et al, 2003;Millette et al, 2008;O'Shea et al, 2012). Several reports describe the beneficial effects of Lactobacillus species on the gastrointestinal tract (Bernbom et al, 2009;Guarner & Malagelada, 2003;O'Callaghan et al, 2012;Walter, 2008).…”
Section: Introductionmentioning
confidence: 99%